Impact of Aging on Empathy: Review of Psychological and Neural Mechanisms - Beadle, Janelle N.; de la Vega, Christine E. (Frontiers in Psychiatry, 2019)
Empathy in aging is a key capacity because it affects the quality of older adults’ relationships and reduced levels are associated with greater loneliness. Many older adults also find themselves in the role of a caregiver to a loved one, and thus empathy is critical for the success of the caregiver–patient relationship. Furthermore, older adults are motivated to make strong emotional connections with others, as highlighted in the socioemotional selectivity theory. Consequently, reductions in empathy could negatively impact their goals. However, there is growing evidence that older adults experience at least some changes in empathy, depending on the domain. Specifically, the state of the research is that older adults have lower cognitive empathy (i.e., the ability to understand others’ thoughts and feelings) than younger adults, but similar and in some cases even higher levels of emotional empathy (i.e., the ability to feel emotions that are similar to others’ or feel compassion for them). A small number of studies have examined the neural mechanisms for age-related differences in empathy and have found reduced activity in a key brain area associated with cognitive empathy. However, more research is needed to further characterize how brain changes impact empathy with age, especially in the emotional domain of empathy. In this review, we discuss the current state of the research on age-related differences in the psychological and neural bases of empathy, with a specific comparison of the cognitive versus emotional components. Finally, we highlight new directions for research in this area and examine the implications of age-related differences in empathy for older adults.